2016
DOI: 10.1142/s1793545816500152
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tumor detection with combined MR–Photoacoustic-Thermoacoustic imaging

Abstract: Here, we report a new method using combined magnetic resonance (MR)-Photoacoustic (PA)-Thermoacoustic (TA) imaging techniques, and demonstrate its unique ability for in vivo cancer detection using tumor-bearing mice. Circular scanning TA and PA imaging systems were used to recover the dielectric and optical property distributions of three colon carcinoma bearing mice While a 7.0-T magnetic resonance imaging (MRI) unit with a mouse body volume coil was utilized for high resolution structural imaging of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Interestingly, the absorption properties of hemoglobin are affected by whether or not it binds to oxygen. By comparing the PA signals of deoxyhemoglobin (Hb), oxyhemoglobin (HbO) and oxygen saturation (sO 2 ) could be calculated in intratumoral and peritumoral areas ( Huang et al, 2016 ; Rich Laurie and Mukund, 2016 ; Dai et al, 2020 ; Jiao et al, 2020 ; Qian et al, 2020 ). In this way, OAI uses endogenous contrast mechanisms to visualize tumor microvascular structure and hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the absorption properties of hemoglobin are affected by whether or not it binds to oxygen. By comparing the PA signals of deoxyhemoglobin (Hb), oxyhemoglobin (HbO) and oxygen saturation (sO 2 ) could be calculated in intratumoral and peritumoral areas ( Huang et al, 2016 ; Rich Laurie and Mukund, 2016 ; Dai et al, 2020 ; Jiao et al, 2020 ; Qian et al, 2020 ). In this way, OAI uses endogenous contrast mechanisms to visualize tumor microvascular structure and hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The actual averaged microwave power density at the surface of rat brain is below 0.32 mW/cm 2 , which is far below the safety standard (10 mW/cm 2 at 3 GHz). 21 …”
Section: Introductionmentioning
confidence: 99%
“…With the publication of above reports, more and more researchers are aware of the advantages of TAI and put their e®orts into improving TAI system. Nowadays, the main TAI groups in this¯eld are Patch et al, [28][29][30][31][32][33] Ntziachristos et al, [34][35][36][37] Jiang et al, [38][39][40][41][42][43] Xin et al, [44][45][46][47][48][49] Arbabian et al, 50,51 Zheng et al, [52][53][54] Xing et al [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] and others. Under the e®orts of these researchers, the excitation source, data acquisition system and image algorithm have been improved greatly, and it can be revealed that TAI is e±cient in detecting the area with anomalous microwave absorption in biological tissue, particularly for breast cancer.…”
Section: Introductionmentioning
confidence: 99%